Physical activity and long-term fatigue among colorectal cancer survivors: a population-based prospective study - Eyl-Armbruster, Ruth Elisa; Thong, Melissa S. Y.; Carr, Prudence R.; Jansen, Lina; Koch, Lena; Hoffmeister, Michael; Chang-Claude, Jenny; Brenner, Hermann; Arndt, Volker (BMC cancer, 2020)
Evidence suggests that physical activity (PA) is beneficial for reducing fatigue in colorectal cancer (CRC) survivors. However, little is known regarding long-term effects of PA on fatigue and whether pre-diagnosis PA is associated with less fatigue in the years after diagnosis. Our study aimed to investigate the association of pre- and post-diagnosis PA with long-term fatigue in CRC survivors.
Gesehen am 24.03.2021